PENGARUH DISIPLIN BELAJAR DAN KREATIVITAS GURU TERHADAP MOTIVASI BELAJAR SERTA IMPLIKASINYA TERHADAP HASIL BELAJAR - Titenia Ita Roswita Kurniawan; Ati Sadiah; Rendra Gumilar (EDUNOMIA: Jurnal Ilmiah Pendidikan Ekonomi, 2025)
Low academic achievement among students remains a pressing issue in the field of education. Both internal and external factors such as learning discipline and teacher creativity are believed to influence students’ motivation and learning outcomes. This study aims to examine the influence of learning discipline and teacher creativity on learning motivation and their implications for student achievement. A quantitative approach was employed using a survey method. The population consisted of 186 Grade XI Social Economics students at SMA Negeri 7 Tasikmalaya. The sampling technique used was non probability sampling with a saturated sampling method. Data were collected through questionnaires. Data were analyzed using Interval Class Value (ICV) and Path Analysis with the assistance of SPSS version 25. The results showed that learning discipline and teacher creativity significantly influence learning motivation. While learning discipline did not have a direct effect on academic achievement, teacher creativity did. Moreover, learning motivation was found to significantly affect academic achievement. Additionally, learning discipline and teacher creativity both had indirect effects on academic achievement through learning motivation. The findings highlight the critical role of psychological and pedagogical factors particularly motivation in enhancing student learning outcomes. This study offers valuable insights for the advancement of educational practices, emphasizing the importance of fostering both student discipline and teacher creativity to support academic success.